Obligations & contracts - Luna, Alden Reuben B. (Intramuros, Manila, Philippines : Unlimited Books Library Services and Publishing Inc., 2019)
This phenomenon is attributable primarily to lack of sufficient exposure to laws governing this facet of our social existence, and secondarily due to the fact that not all obligations and/or contracts are in writing. as customarily believed.
Chapter 1. Obligation: General Principles and considerations -- Chapter 2. Nature and effects of Obligations -- Chapter 3. Kinds of Obligation -- Chapter 4. Plurality of objects and subjects in an Obligation -- Chapter 5. Payment as mode of Extinguishing an obligation -- Chapter 6. Other models of Extinguishing an Obligation -- Chapter 7. Nature of Contracts -- Chapter 8. Forms of Contracts and Defective Contracts.
Includes bibliographical references.
Keywords: CONTRACTS -- PHILIPPINES